Anatomical Considerations related to the Alveolar Antral Artery - asaad, Mounzer (Latakia University Journal -Medical Sciences Series, 2023)
Background: The alveolar antral artery (AAA) is a vascular structure that often passes through the area of lateral window opening during sinus augmentation and can reach dimensions that, if the vessel is severed, can represent a serious complication of the surgical procedure. Purpose: we aimed at summarizing the results obtained from the studies that examined anatomical position and dimension of the AAA in order to give the clinician a reference when planning for a sinus augmentation surgery and other surgeries involving the sinus wall. Materials and Methods: A search of available literature was conducted using electronic databases (PubMed and Medline). Results: Detection rate of AAA on cone beam computerized tomography (CBCT) is variable and may depend upon the experience of the clinician. The course of the vessel is most frequently intraosseous, and its diameter, despite being smaller than 1 mm in most of the cases, can have a high incidence of diameters between 1 mm and 2 mm. Mean distances of the AAA from alveolar crest and sinus floor range from 11.25 mm to 26.90 mm and 5.80 mm to 10.40 mm. Conclusions: Anatomical variants of the AAA that may increase the risk of severe intraoperatory bleeding are frequent and must be detected by the clinician implementing the use of the CBCT.